Increased eating disorder frequency and body image disturbance among fashion models due to intense environmental pressure: a content analysis - Bogár, Nikolett; Kővágó, Pál; Túry, Ferenc (Frontiers in Psychiatry, 2024)
Introduction: Female fashion models are under intense occupational pressure. The present study focuses on assessing the lived experience of fashion models with regards to their dieting and exercising habits, body image perception, eating disorder-like symptoms, and experience of abuse via self-narrated reports.Series of open questions were distributed among international fashion models (N=84, mean age=23.2 years; mean BMI=16.9) selected by convenience and snowball sampling. Models from 17 countries participated. The questions targeted models' eating, exercising, dieting habits, body image perception, and eating disorder symptoms. The average word count of the transcripts was 2473.9 (SD = 2791.6). Thematic content analysis was performed on the transcripts. A total of 31 codes were created to address disordered eating and body image concerns.Results: Negative body-related claims appeared in 89.3%, and positive claims in 64.3% of the models' transcripts. Negative remarks about eating were made by 45.2% of the participants, and 23.8% positively. Control over their food intake was exercised by 78.6% of the participants and 40.5% used extreme calorie restriction. Models who talked more positively about their bodies expressed significantly more frequently extreme calorie restriction. Extreme sports habits occurred in 23.8% of the transcripts, obsessive sports habits were claimed by 11.9% of participants. Self-induced vomiting was prominent in 14.3% of the answers. Criticism from other industry members was experienced by 83.3% of the participants while 44.0% received body appreciation. Body image disorder-like symptoms were expressed by 63.1% of models.Such models mentioned significantly more often content about eating disorders and talked significantly more negatively about eating. Psychological problems were mentioned by 48.8%, whereas 16.7% took part in psychotherapy. Those who partake in therapy mentioned significantly more eating disorder content in their narratives. Abuse was mentioned by 25.0% of the models.Fashion models are experiencing increased environmental pressure to conform to the extreme slimness ideal. There is a heightened prevalence of disordered eating and other weight-controlling behaviours among fashion models to succeed in their careers. Qualitative research is crucial in understanding the more subtle dynamics in conforming to and maintaining the thin beauty ideal